UNEQUAL RESTORATIVE JUSTICE THE PROBLEM OF NEGLECTING THE RIGHTS OF THE REPORTED PARTY IN THE CRIMINAL JUSTICE SYSTEM - Marasabessy , Fauzy; Sugiri, Bambang; Ratnohadi, Heru (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
Restorative justice has been adopted as an alternative approach within the criminal justice system, with the primary aim of restoring relationships between offenders, victims, and the community. However, in practice in Indonesia, the implementation of restorative justice tends to prioritize victim recovery while failing to provide balanced legal protection for the reported party. This imbalance raises serious concerns, particularly in relation to the principle of presumption of innocence and the constitutional rights that should be upheld for every individual involved in legal proceedings. This article aims to analyze the unequal treatment faced by reported parties within restorative justice mechanisms in the criminal justice system. Utilizing a normative juridical approach, the study examines existing regulations and case studies of restorative justice implementation by law enforcement authorities. The findings indicate that the absence of robust procedural standards to safeguard the rights of the reported party renders restorative justice practices vulnerable to abuse, including coercion into settlement or undue pressure. Therefore, regulatory reinforcement and supervisory mechanisms are needed to ensure that restorative justice not only prioritizes victims' interests but also guarantees equal legal protection for reported parties, thereby contributing to a fair and balanced criminal justice system.